Multiple Load Characteristic Analysis for Interacted and Interconnected Micro Grid on Pelagic Clustering Islands. Issue 1 (January 2021) - Hou, Ting-ting; Zou, Yu-xin; Chen, Zhu; Ding, Heng; Fang, Reng-cun; Lei, He; Yang, Dong-jun; Sang, Zi-xia
Abstract: With the gradual emphasis on the development and utilization of islands, the energy supply problem of islands far away from land-based has become increasingly prominent. Based on the traditional single energy acquisition method, this paper establishes an island independent energy cycle system with high reliability power exchange ship as the main part, tidal energy and photovoltaic power generation as the auxiliary. It has opened up an effective way to meet the needs of military life and production on the island.